AI in action: Advancing EFL writing skills and teachers’ perceptions - Ali Al Ghaithi; Behnam Behforouz (Universitas Syiah Kuala, 2026)
The current study aimed to measure the perceptions of English as a foreign language (EFL) teachers regarding the use of AI tools in the writing process; concurrently, it investigated the impact of these AI tools on EFL learners` writing performance. A total of 120 Omani pre-intermediate EFL learners were assigned to two control and experimental groups for a 4-week treatment length. Although both groups received similar in-class training for their writing skills, the experimental group used various AI tools such as Gemini, ChatGPT, Copilot, EditGPT and Grammarly as facilitators to receive extra practice and feedback on their writing pieces. The statistical analysis of the writing tasks pretests and posttests based on Mann-Whitney U test revealed that the experimental group performed remarkably better than the control group participants, which could be attributed to the positive impact of AI tools. Additionally, a researcher-made perception questionnaire was administered to the teachers after the treatment period, and the responses indicated that using AI tools can positively influence the grammatical and lexical knowledge of the learners, encourage the students to revise and change their tasks, and finally, increase the confidence level among the learners. The findings of this study are helpful for teachers, such as providing higher-order writing skills, students, such as fostering self-correction, and institutions, like integrating artificial intelligence tools within the writing courses.